Makna Estetika dan Stilistika dalam Perspektif Bahasa terhadap Syair dan Lirik Lagu Ebiet G. Ade Berjudul Aku Ingin Pulang - Ririn Pratiwi Suharto (Signifiѐ, 2023)
The lyrics of the song written by Ebiet G. Ade entitled I Want to Go Home are very interesting to study because they contain aesthetic and stylistic values. This research aims to identify the aesthetic meaning and stylistic meaning in the lyrics of the song written by Ebiet G. Ade entitled I Want to Go Home. This research uses two methods, namely aesthetic model research and linguistic style research. The research results show that Ebiet G. Ade's songs contain ontological beauty and psychological aspects, stylistic definitions, and also aesthetic value. Its meaning refers to representing a person's longing to return home to the Creator. reflects a person's longing for the Creator.